CREATIVE WRITING AS A TOOL IN TEACHING ENGLISH - Kurbaniyazova, S. (SCIENCE and SOCIETY, 2022)
The article discusses the concept of creative writing skills and explains their contribution as a tool for teaching and learning English. Describes how poems can be effectively used in English classes to reinforce students’ knowledge of English - vocabulary and grammar - and encourage their creative writing. It also shows the importance of using creative writing assignments in an academic environment.